Isolation and Molecular Screening of Fungus as Agents in Cellulolytic Transformation Materials from Symbiotic Lichen - Rahardiyan, Dino; Moko, Emma Mauren (Biosaintifika: Journal of Biology & Biology Education, 2023)
The abundance of lignocellulosic waste makes it a potential source for advanced biomaterials through various transformation processes. Lignocellulosic biomass transformation to advanced biomaterials involves enzymes from extracellular metabolites of microorganisms capable of hydrolyzing lignocellulose. This research was to molecularly screen fungi found in symbiotes of lichen endemic to trees growing in North Minahasa (North Sulawesi) with lignocellulolytic transformation enzymes. Molecular screening was conducted from identified fungi isolates based on partial genetical analysis on the locus of Internal Transcribed Spacer (ITS) of the fungi’s ribosomal DNA. Fungi isolates screening identified Trichoderma koningiopsis (isolate HZA8 and isolate HZA6), Penicillium sumatraense (strain CBS 127365 and strain CBS 130380), Trichoderma hamatum (isolate PAN12-45 and isolate PAN12-05), Aspergillus aculeatus (strain A1.9 18S),  Aspergillus aculeatus (isolate XSD-74), Trichoderma reesei (strain S2606 and isolate 5A14).  Molecular identification and BLAST homology of potentially lignocellulolytic fungi isolates rDNA indicated that isolate KB2 had close relationship with Trichoderma reesei at 100% degree of closeness and an index of cellulolytic activity of 1.19. While isolate KB3 appeared closely related to Aspergillus aculeatus at 99.83% degree of closeness and an index of cellulolytic activity of 1.57. Therefore, the potential of developing bioprocess industries in general and in particular is most probable.